Patterns of substance use initiation among Indigenous adolescents() - Whitbeck, Les B. (Addict Behav, 2015)
BACKGROUND: The data for this study come from an eight-wave panel study of Indigenous (Canadian First Nations and American Indian) adolescents from three U.S. reservations and four Canadian reserves. OBJECTIVES: Our objective was to investigate variations in patterns of substance use initiation from early adolescence through early adulthood using data collected annually for 8 years. METHOD: At baseline the sample included 675 Indigenous adolescents (M age = 11.10, SD = .83; 50.3% girls). First, we calculated cumulative rates of substance use initiation by age. We then examined whether the cumulative initiation rates were moderated by gender using logistic regression analyses. Second, we calculated hazard rates for substance use initiation by age. Third, we focused on the ordering of two substances, paired two substances, and three substance initiation sequences. RESULTS: If one looks only at the cumulative rates of substance use initiation there appears to be support for a sequential progression of substance use during early adolescence. In contrast to the cumulative rates of substance use initiation, the hazard analyses showed a much more mixed, less progressive sequence. Among two substance pairings a nicotine to marijuana initiation sequence was most likely, followed by a nicotine to alcohol sequence. An alcohol to marijuana sequence was nearly twice as likely as a marijuana to alcohol sequence. Refined analyses to conform to those of many of the traditional gateway studies by introducing paired two substance orderings indicated that nicotine and/or alcohol prior to marijuana use was by far the most likely sequence. In two of the three most likely three substance sequences (nicotine to alcohol to marijuana and nicotine to marijuana to alcohol) nicotine was the first substance initiated. CONCLUSION: This study refines the gateway hypothesis for Indigenous adolescents by providing an in-depth analysis of substance use initiation. The only evidence for a “gateway” substance that emerged in our analyses was for nicotine use which was likely to precede alcohol and marijuana use in both two-substance pairings and to a lesser extent in three-substance initiation sequences.